2021
DOI: 10.1002/dad2.12157
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of an Alzheimer's disease risk assessment program in a primary care setting

Abstract: Introduction The goal of this study was to pilot a referral‐based cognitive screening and genetic testing program for Alzheimer's disease (AD) risk assessment in a primary care setting. Methods Primary care providers (PCPs; N = 6) referred patients ( N = 94; M = 63 years) to the Rhode Island Alzheimer's Disease Prevention Registry for apolipoprotein E (APOE) genotyping and cognitive screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Given that Black and Hispanic adults are at increased risk for dementia, improving access to risk information for these groups may facilitate greater interest in prevention research. For example, a recent pilot study of an AD risk assessment program in a primary care setting found the intervention yielded a more demographically diverse sample than an AD prevention registry ( 34 ), suggesting this approach may be a potential method to improve recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Black and Hispanic adults are at increased risk for dementia, improving access to risk information for these groups may facilitate greater interest in prevention research. For example, a recent pilot study of an AD risk assessment program in a primary care setting found the intervention yielded a more demographically diverse sample than an AD prevention registry ( 34 ), suggesting this approach may be a potential method to improve recruitment.…”
Section: Discussionmentioning
confidence: 99%
“… 40 One study has noted the feasibility of such screening interventions. 30 However, in UK-based population studies, the most common recommendation was to embed proactive approaches in routine health check-ups, for example, the annual health review of older adults. 27 GPs in this study mirrored this suggestion and would require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's Disease International (ADI) (39) recommends introducing annual brain health check-ups to those aged 50 and over, providing focused opportunities to promote dementia risk reduction (39). Some initial studies have noted the feasibility of such screening interventions (30). However, in UK-based population studies, the most common recommendation was to embed proactive approaches in routine health check-ups, e.g., the annual health review of older adults (27).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We found that participants were willing to increase healthy lifestyle behaviors if they could achieve “moderate” risk reduction for dementia (between 21% and 23%). The fact that adults may be willing to engage in healthy lifestyle behaviors with the potential for even moderate risk reduction has implications for counseling at-risk individuals28 and potentially reducing dementia prevalence, given that up to one third of AD cases could be attributed to modifiable causes such as smoking, poor diet, and lack of exercise 5. Clinicians may consider exploring perceptions of dementia risk reduction with their patients in order to identify individualized factors that could enhance engagement in healthy lifestyle behaviors, as there was variability in our sample, with some participants willing to change behavior to achieve only mild risk reduction, while others reported a more substantial risk reduction would motivate them to shift behavior.…”
Section: Discussionmentioning
confidence: 99%